Análisis para la automatización de procesos, para la venta de insumos agrícolas para, la empresa “Banagric” a través de un aplicativo web. - Pereira Quisintuña, María Elizabeth (2022)
The proposal raised by this research is to develop a web application, which involves the staff that works, and through these strategies such as: Improving the sales process and promoting staff training to be a competitive company, enhance the presence of BANAGRIC products with an adequate sales planning, which allows it to increase its profitability, increase notoriety and improve the image of BANAGRIC in the clients, through a promotion plan and obtaining recognition of the company in the different banana growers. Given that the company seeks to promote the sales of its products through the implementation of the Application with web environment characteristics which has been developed to automate the marketing of its products and thus facilitate the work of the company's staff and in turn provide a better service to each of the users since the processes will be carried out with greater speed and security than their requested orders arrive. The web design will allow each of the users to access from any device that has internet to carry out the respective verifications of the commercial processes. This design will allow us to promote the products and thus use it 7 days a week, at any time of the day and in any place, we will be able to place our orders immediately and with the comfort that every banana producer wants.